UNCONTROLLED PHOTOMULTIPLIER CURRENT IN PHOTOEMISSION ANALYSIS - K. A. Viazava; K. N. Kasparov; O. G. Penyazkov (Приборы и методы измерений, 2016)
The dependence of photon energy from energy of photoelectron is base of photoemission radiation analysis. In such photoemission measurements except current of photocathode is always exist a reverse current from the collector of electrons to the photocathode in two-electrode sensors. There are various ways of reverse and uncontrolled current eliminating or reducing their influence. The constructive method is based on creating an electron-optical system of photoelectronic device, which would be a photoelectron energy analyzer. The second method – technological. However, it requires the manufacture of the photocathode and the dynode system in different vacuum chamber with subsequent connection to a single device in vacuum environment without exposure to the atmosphere. The purpose of this article is to determinate the effect of photoemission from photocathode chamber and the first dynode of photomultiplier on energy distribution of the photoelectrons from photocathode. To solve this problem authors obtained calibration curves for measuring pyrometer module ПИФ 4/2 with ФЭУ-114 as a sensor at supply voltage 1350 V and different decelerating voltages. The effect of illumination on the value of modulation coefficient on temperature k(T) and wavelength k(λ) is shown. In temperature measurements, this effect is evident in fact that at temperatures below 1400 K linear dependence ln k – T-1 is broken. Still this linear dependence is a necessary consequence of the fact that the measured temperature is color temperature. However, this calibration curve can be used to measure low temperature if the target measurements condition and calibration conditions are identical. In wavelength calibration, curve k(λ) at λ > 760 nm is two-valued, that doesn’t allow to identify monochromatic radiation by this method and bring in errors in temperature measurements.